DEVELOPMENT OF KNOWLEDGE MANAGEMENT STRATEGIES FOR PROPERTY MANAGEMENT COMPANIES IN MALAYSIA - Razali, Muhammad Najib; Yim Mei, Janice Lee; Zainuddin, Ainur Zaireen; Mohd Yunus, Norhidayah (Journal of Technology Management and Business, 2016)
This paper attempts to develop a knowledge management (KM) framework concept that can be used by property management companies in Malaysia. KM is a management method that consists of people, information technology (IT) and organisational elements to capture information, which is an organisationâ€™s most valuable asset. Hence, it is believed that this study will contribute to the betterment of the real estate industry. The research findings suggest several magnitudes as well as an inclusive set of KM strategy activities that can be adopted by property management companies in Malaysia. The study, however, underpinned its findings based upon a limited number of samples. Only 16 out of 25 registered property management companies participated in the research, representing a small proportion of property management establishments that are registered under the Board of Valuers, Appraisers and Estate Agents, being the professional body that governs property management practices in Malaysia. This study proposes a KM strategies framework as a guideline for property management companies to embrace KM principles. The findings have showed that most of the strategies were significant to the property management companies in Malaysia. Nine strategies based on rankings were identified as very suitable and essential in order to ensure the success of the framework to the companies. Research in this area, which focuses on the practice of property management, is extremely rare, thus justifying its uniqueness within the existing body of knowledge.Â Keywords: Knowledge management, Malaysia, property management companies, strategies